Nuclear DNA content variation within four species of Asian catfish of family Pangasidae and their two interspecific hybrids by flow cytometry - Imron; Evi Tahapari; Jadmiko Darmawan; Muhammad Luthfi Abdurachman (Jurnal Akuakultur Indonesia)
Nuclear DNA content (NDC) of species or population is believed to have been formed naturally by many mechanisms such chromosomal mutation, insertion and deletion, transposable element, and duplication. Additionally, hybridizations and species’ phylogenetic relationship may also contribute to the NDC diversity. This study was aimed to investigate the profile of NDC in four species Asian catfishes of the genera Pangasius including Pangasionodon hypophthalmus,  Pangasius djambal, Pangasius nasusutus, Pangasius nieuwenhuisii, interspecific hybrid of female P. hypophthalmus and male P. djambal (Hybrid HD),  and female P. hypophthalmus and male P. nasutus (Hybrid HN). Red blood cells (RBC) were taken from the respective species/groups and NDC measurement was performed in an Attune acoustic flowcytometer (ABI) using DAPI staining and chicken, Gallus domesticus, RBC was used as size reference. The results showed that the mean NDC of P. hypophthalmus, P. djambal. P. nasusutus, P. nieuwenhuisii, were 0.960±0.0254 pg, 1.017±0.0510 pg, 1.000±0.0410 pg, 1.074±0.0231 pg, which are within the range of NDC in the other catfish families The NDC values of Hybrid HD and Hybrid HN were1.005±0.0358 and 0.956± 0.0089, respectively. Among the pure line species, the NDC of P. hypophthalmus was the lowest and was different (P<0.05) from those of P. djambal and P. nieuwenhuisii but was not different (P>0.05) from that of the P. nasutus. The NDC of both Hybrid HD and Hybrid HN were not different form their respective parental lines. However, the NDC profiles of both hybrids were different in that the NDC of the former was in between while the latter was below their respective parental lines. Phylogenetically, the NDC diversity within Pangasiid catfish in this study was independent of their phylogenetic relationship based on cytoplasmic and nuclear markers.